ESTIMATION OF PB AND TOTAL SUSPENDED SOLID (TSS) CONCENTRATION BASED ON REMOTE SENSING DATA - Girsang, Dhea Vonisa; Yuliara, I Made; Ratini, Ni Nyoman (Universitas Mataram, 2023)
Research has been carried out on the comparison of the concentration of Pb and Total Suspended Solid (TSS) of laboratory test results with Sentinel-2A satellite image data recorded on August 25, 2021 at the Suwung estuary dam, Denpasar city. The method used to compare the 2 measurement results is through testing by paired sample correlation and the graph. The result from the measurement show that the TSS value between Sentine-2A and laboratory has a fairly close value but the Pb value between Sentinel-2A and the laboratory have a much differences. The differences of the value between Sentinel-2A images and laboratory data can be caused by differences in the image recording time and field data collection time. This can result in changes or dynamics of water conditions that result in changes in the value and distribution Pb and then the radiometric influence of differences in Pb values ​​on images and laboratory data can be caused by radiometric influences or interference with wave propagation in the air.